2008
DOI: 10.1039/b719542g
|View full text |Cite
|
Sign up to set email alerts
|

Platination of full length tRNAAla and truncated versions of the acceptor stem and anticodon loop

Abstract: Nuclear DNA is a well characterized target for many low molecular metal-based drugs, with cisplatin and related antineoplastic compounds as typical examples. Much less is known concerning to what extent targeting of RNA may influence the activity spectrum of these types of drugs. In a preliminary communication by us (Papsai et al., Dalton Trans., 2006, 3515) we were able to show that the folded, three-dimensionally well defined structure of tRNA(Ala) readily interacts with cisplatin. In the present study we ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…Several examples of covalent binding of platinum complexes to RNA have been herein commented [44,45,47,70,[76][77][78][79][80][81][82][83][84][85][86][87]. Even if the existence of platinum-RNA adducts is undeniable, further biochemical and structural studies are needed to better understand the nature of platinum-RNA adducts as well as their impact on RNA structure and on RNA biological functions.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Several examples of covalent binding of platinum complexes to RNA have been herein commented [44,45,47,70,[76][77][78][79][80][81][82][83][84][85][86][87]. Even if the existence of platinum-RNA adducts is undeniable, further biochemical and structural studies are needed to better understand the nature of platinum-RNA adducts as well as their impact on RNA structure and on RNA biological functions.…”
Section: Discussionmentioning
confidence: 95%
“…This preassociation precedes covalent interaction [90,91], and was shown to influence the binding kinetics also in model systems using short single-stranded DNAs [92]. This finding suggests that short RNAs may also represent good targets for cisplatin [77,78], and prompted further studies to better elucidate the basis of platinum-RNA interaction. Interestingly, in vitro studies performed using mono-aquated platinum complexes have shown that RNA platination kinetically competes or is even preferred over DNA platination [80,93].…”
Section: Platinum Binding To Rnamentioning
confidence: 88%
See 3 more Smart Citations